General chemistry for engineers - Gaffney, Jeffrey S., 1949- (Elsevier, 2018)
General Chemistry for Engineers explores the key areas of chemistry needed for engineers. This book develops material from the basics to more advanced areas in a systematic fashion. As the material is presented, case studies relevant to engineering are included that demonstrate the strong link between chemistry and the various areas of engineering.